Determination of optimum sett size for white guinea yam (Dioscorea rotundata Poir.) seed yam production: trends in sprouting in the presprout nursery and field performance - Gyansa-Ameyyaw, C.E.; Hahn, S.K.; Álvarez, M.N.; Doku, E.V. (International Society for Horticultural Science, 1994)
Six weight-classes of white guinea yam (Dioscòrea rotundata Poir.) setts—2–5, 5.01–10, 10.01–20, 20.01–30, 30.01–40, and 40.01–50 g—were presprouted in fresh, moist sawdust in open-air, propagation beds. The 2–5 g and 5.01–10 g classes were described as microsetts. Three natural groups patterned along the various phases of the sigmoid curve, within which the classes did not perform differently were evident at 26 days after planting (DAP), for sets at the leafy-and leafless-shoots stage. The group I classes were: 20.01–30 g, 30.01–40 g, and 40.01–50 g, while group II comprised the 5.01–10 g and 10.01–20 g classes. Group III had the 2–5 g class. Two significantly dissimilar groups were observed for harvest index (HI) at 3 months after transplanting (MAT): group I consisted of the 20.01–30 g, 30.01–40 g, and 40.01–50 g classes while the 2–5 g, 5.01–10 g, and 10.01–20 g, were in group II. The group I remained unchanged as regards total fresh tuber yield. Differences existed, however, within Group II: the 10.01–20g class produced significantly greater tuber yields than the 2–5 g class. However, yields of the 5.01–10 g class, was not significantly different from that of the 10.01–20 g or the 2–5 g class. Considering the sprouting in the presprout nursery and the fact that the plants under the 2–5 g treatment senesced early at 4 MAT, after succumbing to a leaf necrotic disease, the 5.01–10 g class representing the upper range of the microsetts is best for seed yam production.